2013
DOI: 10.1007/s10571-013-9999-3
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Efficacy of Cell-Penetrating Peptides TAT, Penetratin, Arg-9, and Pep-1 in Glutamic Acid, Kainic Acid, and In Vitro Ischemia Injury Models Using Primary Cortical Neuronal Cultures

Abstract: Cell-penetrating peptides (CPPs) are small peptides (typically 5-25 amino acids), which are used to facilitate the delivery of normally non-permeable cargos such as other peptides, proteins, nucleic acids, or drugs into cells. However, several recent studies have demonstrated that the TAT CPP has neuroprotective properties. Therefore, in this study, we assessed the TAT and three other CPPs (penetratin, Arg-9, Pep-1) for their neuroprotective properties in cortical neuronal cultures following exposure to glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 31 publications
7
58
0
2
Order By: Relevance
“…However, several years ago, we and others demonstrated that TAT possesses intrinsic neuroprotective properties both in vitro in neurons exposed to excitotoxicity and oxygen-glucose deprivation (OGD) and in vivo following cerebral ischaemia in P12 rats after intraventricular injection (Craig et al, 2011;Meade et al, 2010a, b;Vaslin et al, 2009b;Xu et al, 2008). We subsequently showed that poly-arginine-9 (R9), penetratin and Pep-1 also display neuroprotective actions in in vitro excitotoxic and/or OGD models (Meloni et al, 2014). Furthermore, our data showed that R9 and penetratin were 17-and 4.6-fold respectively more neuroprotective than TAT (Meloni et al, 2014).…”
Section: Arginine-rich Cell Penetrating Peptides and Intrinsic Neuropmentioning
confidence: 74%
“…However, several years ago, we and others demonstrated that TAT possesses intrinsic neuroprotective properties both in vitro in neurons exposed to excitotoxicity and oxygen-glucose deprivation (OGD) and in vivo following cerebral ischaemia in P12 rats after intraventricular injection (Craig et al, 2011;Meade et al, 2010a, b;Vaslin et al, 2009b;Xu et al, 2008). We subsequently showed that poly-arginine-9 (R9), penetratin and Pep-1 also display neuroprotective actions in in vitro excitotoxic and/or OGD models (Meloni et al, 2014). Furthermore, our data showed that R9 and penetratin were 17-and 4.6-fold respectively more neuroprotective than TAT (Meloni et al, 2014).…”
Section: Arginine-rich Cell Penetrating Peptides and Intrinsic Neuropmentioning
confidence: 74%
“…In in vitro studies, cell-penetrating peptides were recently reported to protect dissociated cortical neurons against excitotoxic doses of NMDA (50,51). Furthermore, Meloni et al (49) reported that only long Arg-rich peptides, containing nine or more arginines, demonstrated neuroprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on arginine-rich peptides showed a key role of guanidium side chains of arginine residues for cellular uptake (Futaki et al, 2013). Recently, a new class of cell-penetrating peptides represented by the short peptide Xentry (LCLRPVG) derived from an N-terminal region of the X protein of Hepatitis B virus has been described (Meloni et al, 2014) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%